2003
DOI: 10.1034/j.1601-183x.2003.00012.x
|View full text |Cite
|
Sign up to set email alerts
|

A rating scale for wildness and ease of handling laboratory mice: results for 21 inbred strains tested in two laboratories

Abstract: Rating scales for difficulty in capturing and holding mice were devised that proved to be easy to use and highly sensitive to differences among mouse strains on the A and B priority lists of the Mouse Phenome Project. The simplicity of the scales makes it feasible to rate wildness during behavioral test sessions without adding much to testing time or distracting the technician from the principal task at hand. Overall wildness and placidity ratings obtained by combining capture and hold ratings provide a good i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
80
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(84 citation statements)
references
References 13 publications
3
80
1
Order By: Relevance
“…Crabbe, Wahlsten, and colleagues [12,47,49,50] have provided compelling evidence that results from behavioral testing can significantly differ between laboratories, even when procedures, animal source, and other environmental factors are carefully controlled and standardized. Discrepancy of findings may be greater in tests related to anxiety-like behavior [47].…”
Section: Discussionmentioning
confidence: 99%
“…Crabbe, Wahlsten, and colleagues [12,47,49,50] have provided compelling evidence that results from behavioral testing can significantly differ between laboratories, even when procedures, animal source, and other environmental factors are carefully controlled and standardized. Discrepancy of findings may be greater in tests related to anxiety-like behavior [47].…”
Section: Discussionmentioning
confidence: 99%
“…Strain differences are commonly acknowledged to affect many biological variables; for example, searching the Institute of Scientific Information (ISI) Web of Science for the terms 'strain differences' and 'rats' revealed 725 records. In contrast, extensive searching for animal unit differences yielded just two meta-analyses (Haseman & Rao 1992, Kafkafi et al 2003 and seven crosslaboratory experiments (Lee & McClintock 1986, Crabbe et al 1999, Salome et al 2002, Masaya et al 2003, Wahlsten et al 2003a,b, Wolfer et al 2004. All of these studies, except one (Wolfer et al 2004), found important inter-laboratory effects.…”
Section: Animal Unitmentioning
confidence: 99%
“…The main question asked during such characterisation relates to the abilities of a mouse genome to cope with the presence of an expressed transgene protein. The existence of possible effects due to strain genetic background, modifier genes, compensatory effects, and/or subtle differences in the experimental paradigms, including the strains' different response to handling (133), can yield different, often contradictory results. Therefore, a broad characterization of mouse behaviour, including both hippocampus-independent memory systems (134)(135)(136) and other non-cognitive behavioural systems, such as changes in agitation and aggression levels (137), locomotor, exploratory, or stereotypic activity (138) can be very useful in evaluating transgenic mice.…”
Section: Evaluation Of Mnemonic Functionmentioning
confidence: 99%